2021
DOI: 10.1111/1750-3841.15951
|View full text |Cite
|
Sign up to set email alerts
|

Policosanol alleviates hepatic lipid accumulation by regulating bile acids metabolism in C57BL6/mice through AMPK–FXR–TGR5 cross‐talk

Abstract: Policosanol exhibits a lipid accumulation alleviating effect, but the underlying mechanisms remains unclear. Bile acids are a significant factor in regulating cholesterol and lipid metabolism homeostasis in mammals. This study was aimed to elucidate the alleviating effect and underlying mechanisms of policosanol on hepatic lipid accumulation through bile acid (BA) metabolism. Policosanol supplementation significantly reduced hepatic triglycerides (19.29%), cholesterol (30.38%) in high fat diet (HFD) induced ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 44 publications
2
8
1
Order By: Relevance
“…1 Over the past few decades, some bile acids have been used as nutrients, feed additives, and clinical therapeutic supplements owing to their roles in blood lipid regulation, intestinal injury recovery, and immune enhancement. 2–5…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Over the past few decades, some bile acids have been used as nutrients, feed additives, and clinical therapeutic supplements owing to their roles in blood lipid regulation, intestinal injury recovery, and immune enhancement. 2–5…”
Section: Introductionmentioning
confidence: 99%
“…1 Over the past few decades, some bile acids have been used as nutrients, feed additives, and clinical therapeutic supplements owing to their roles in blood lipid regulation, intestinal injury recovery, and immune enhancement. [2][3][4][5] Intestinal epithelial homeostasis relies on the balance between cell proliferation and cell death. 10 Cell proliferation is essential for driving intestinal epithelial renewal and injury repair.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that activation of AMPK inhibits the transcriptional activity of FXR and downregulates SHP. 35 , 36 Thus, the changes we observed in the FXR-SHP-CYP7A1 pathway may be attributed to activation of AMPK by NgBR overexpression. Taken together, we determined the mechanism by which NgBR regulates AMPKα activation and the NgBR overexpression-activated SR-BI and bile acid synthesis pathways may be regulated by AMPKα activation.…”
Section: Discussionmentioning
confidence: 80%
“…It was reported that the prevention of hepatic lipid accumulation in obese mice can be achieved through many ways. For instance, policosanol attenuated hepatic lipid accumulation in mice by regulating AMPK-FXR-TGR5 cross-talk ( 43 ). In addition, Han et al have testified that the depletion of gut microbiota could suppress hepatic lipid accumulation in HFD-fed mice ( 44 ).…”
Section: Discussionmentioning
confidence: 99%